Carbon Dioxide (CO2) emission, energy consumption and economic growth: Evidence from selected Southeast Asia countries / Nur Hafizah Ismail … [et al.] - Ismail, Nur Hafizah; Nayan, Sabri; Kadir, Norsiah; Mat Yusoff, Mohd Yushairi (Universiti Teknologi MARA Selangor, 2020)
Southeast Asia countries have experienced rapid economic growth within the past decades with a significant increase in energy dependency and carbon dioxide (CO2) emissions. Continuous development in the urban area has stimulated a rise in energy consumption in many Southeast Asia countries, which resulted in an improvement of citizen's lifestyles and living standards due to increasing income and population. Understanding the relationship between economic growth, energy consumption, and carbon dioxide emissions help economies in formulating energy policies, enhancing energy security and developing a sustainable energy resource. Therefore, this study focuses on the economic growth, energy consumption and carbon dioxide emissions evolved in Southeast Asia by using Environment Kuznets Curve theory. This paper could be useful and beneficial for the Southeast Asia countries to form appropriate environmental policies to maintain the balance of energy demand and supply and to deal with environmental quality issues.